Uncertain Travel Times and Activity Schedules under Conditions of Space-Time Constraints and Invariant Choice Heuristics. (December 2014) - Rasouli, Soora; Timmermans, Harry J P
The aim of this paper is to assess the impact of uncertain travel times as reflected in travel time variability on the outcomes of individuals' activity-travel scheduling decisions, assuming they are faced with fixed space-time constraints and apply the set of decision rules that they have developed over time by learning how to cope with uncertainty in their environment. Features of resulting activity-travel patterns are compared for different travel times. Results of the analyses indicate that uncertain travel times are reflected primarily in changes in the start and end time of activities and the corresponding duration of activities. There is also evidence that some activities are cancelled, suggesting that increased travel times may have made some activity agendas unfeasible.